Simetria discreta 'S IND. 3' como uma possível extensão para o Modelo Padrão - Costa, Pedro Contino da Silva [UNESP] (2014)
A new phase of measures for the mixing angles for the lepton sector began. The latest data for the value of 'teta IND. 3' excluded its null value in more than '10 IND. 'sigma'', then discarding the TBM mixing matrix of leptons. The known Fritzsch texture, used to calculate the mixing angles of quarks, provides extensive empirical agreement for the current values of the angles, as well as for differences in masses of neutrinos. The discrete symmetries 'S IND. 3', together with the Abelian symmetries 'Z IND. 3' e 'Z IND. 5' and are combined together to form the group flavor 'G IND. F' ='S IND. 3' x 'Z ind. 5' x 'Z IND. 3' that aims to expand the usual symmetry of the Standard Model G = 'SU(3) IND. c' x 'SU(2) IND. L x 'U(1) IND. Y', this extension occurs with an increase of five scalar fields which are singlet of SU(2). The main purpose to the inclusion of 'G IND. F' is to make the texture of Fritzsch need not be imposed as a starting point in the mass matrices of charged leptons and neutrinos, but they result in the Yukawa sector after symmetry breaking. Our goal here is to analyze since extension of the MP by the inclusion of the masses of the neutrinos, also exploring the possibility that its be Dicac’s particle or Majorana’s particle and finally the latest test data of 'teta IND. 13'. At the end, we will see the extension of the Standard Model with the group of flavor 'G IND. F' ='S IND. 3' x 'Z ind. 5' x 'Z IND. 3', only analyzing the lepton’s sector leading us to the Fritzsch texture, but with small deviations